Car Rental Business Development Strategy at PT. Perdana Satria Trans (Perdana Rent Car) with a Business Model Canvas Approach - Dimas Prasetyahani (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze the formulation of the Business Model Canvas at PT. Perdana Satria Trans (Prime Rent Car). And also find out the BMC innovations carried out by PT. Perdana Satria Trans (Perdana Rent Car) uses an effective SWOT analysis in the Central Java region. This research method is qualitative. Informants in this study were the leadership and management of PT. Perdana Satria Trans (Prime Rent Car). Collecting data using interviews and documentation studies. Data analysis used the Miles and Huberman method. The results of the study found nine elements of BMC belonging to PT. Perdana Satria Trans (Perdana Rent Car) can be analyzed according to each element. Business innovation on the nine elements of BMC using a SWOT analysis conducted by PT. Perdana Satria Trans (Perdana Rent Car) consists of four strategies.value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnership and cost structure. ST strategy can be applied to aspects ofvalue propositions and revenue streams. The WT strategy can be applied to aspects ofcustomer segments and property value propositions PT. Perdana Satria Trans (Prime Rent Car). Keywords: Business Model Canvas, Car Rental Business, SWOT Analysis